Maternal age-related declines in live birth rate following single euploid embryo transfer: a retrospective cohort study - Wei Jiang; Zichen Zheng; Nan Yan; Shuang Yao; Qijun Xie; Danyu Ni; Shanren Cao; Chun Zhao; Xiufeng Ling (Journal of Ovarian Research)
Abstract Purpose To assess whether maternal age influences the pregnancy outcomes after single frozen euploid embryo transfer. Methods This retrospective analysis was conducted on 1037 cycles of single euploid embryo transfer performed at Nanjing Women and Children’s Healthcare Hospital between January 2016 and April 2023. Patients with severe uterine pathologies, immune disorders, or endocrine diseases were excluded. The cycles were categorized into three age groups: <35 years, 35–37 years, and ≥ 38 years. Primary outcomes included live birth rate, clinical pregnancy rate, early pregnancy loss, and miscarriage rate. Data were analyzed using multivariable logistic regression with generalized estimating equations (GEE) to account for confounding factors and restricted cubic splines to visualize the relationship between maternal age and pregnancy outcomes. Results Women aged ≥ 38 years demonstrated a significantly diminished live birth rate (41.7%) ,which was lower than that observed in women aged < 35 years (54.5%) and 35–37 years (54.0%), with statistical significance (P < 0.05). Multivariable regression analysis revealed that compared with women aged ≥ 38 years, younger women had reduced risk of miscarriage (aOR = 0.371, 95% CI: 0.139–0.988 for the < 35 years group; aOR = 0.317, 95% CI: 0.106–0.954 for the 35–37 years group) and increased likelihood of live birth (aOR = 2.188, 95% CI: 1.154–4.147 for the < 35 years group; aOR = 2.239, 95% CI: 1.0103–4.548 for the 35–37 years group) after adjusting for relevant confounders. Additionally, the analysis showed that embryos biopsied on day 5 were linked to higher clinical pregnancy rates than those biopsied on day 6, and high-grade blastocysts were associated with superior pregnancy outcomes. Conclusion Advanced maternal age is associated with a higher miscarriage rate and lower live birth rate following euploid embryo transfer. Despite the exclusion of aneuploidy, age-related factors beyond chromosomal abnormalities appear to impact reproductive outcomes.